2000
DOI: 10.1677/joe.0.1670363
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes of the oestrogen receptor-alpha and -beta mRNAs in the female reproductive organ of the rat--an analysis by in situ hybridization

Abstract: This study employed an in situ hybridization technique to compare the cellular expression of oestrogen receptor (ER) subtypes, ER and , in the female reproductive organ of the rat during prenatal and postnatal periods. Diffuse signals of ER and mRNAs were co-expressed in the foetal ovary; they were weak and inconsistent before onset of gonadal differentiation, but increased in intensity with age. ER mRNA signals in the ovary sharply increased in intensity to adult levels by postnatal days 6-7, whereas those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…Species-specific differences could also explain the expression of ERα in the Mullerian duct of fetal mice (Nielsen et al, 2000) and rats (Mowa and Iwanaga, 2000), while in the fetal porcine Mullerian duct only ERβ was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific differences could also explain the expression of ERα in the Mullerian duct of fetal mice (Nielsen et al, 2000) and rats (Mowa and Iwanaga, 2000), while in the fetal porcine Mullerian duct only ERβ was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Two in situ hybridization studies revealed similar negative results in the epithelium and mesenchyme of the Müllerian duct throughout the prenatal period in rats and mice (Lemmen et al, 1999;Mowa and Iwanaga, 2000b). However, in the RT-PCR study, rat Müllerian duct ERβ1 and ERβ2 mRNAs were detected and found to be expressed at constant levels from 15.5 dpc to 21.5 dpc (Okada et al, 2002a).…”
Section: During Prenatal Development Of the Müllerian Ductmentioning
confidence: 81%
“…Greco and co-workers (1991) reported that ER immunoreactivity was observed in epithelial cells of female mouse reproductive tract at 15 days post-coitus (dpc), but was occasionally observed at 17 dpc and on the day of birth. The results of immunohistochemistry with a monoclonal antibody specific to ERα in mice (Nielsen et al, 2000), and in situ hybridization with a radio-labeled probe specific to ERα in rats (Mowa and Iwanaga, 2000b) demonstrate that ERα localization varies with the region of the Müllerian duct involved. Nielsen et al (2000) detected a faint immunopositive signal in the nuclei of the surrounding cells of the Müllerian duct as early as 11.5 dpc in mice.…”
Section: During Prenatal Development Of the Müllerian Ductmentioning
confidence: 97%
See 1 more Smart Citation
“…Excluding some splicing variants, two major estrogen receptor (ER) forms, namely ERα and ERβ are expressed in both the epithelial and stromal cells of the rodent uterus [21][22][23][24][25][26][27]. Although ERβ is detected to a lower level and exclusively in the late phase of gestation, both forms are expressed throughout gestational development in a temporalspecific manner [5].…”
Section: Introductionmentioning
confidence: 99%